Implementasi Tanggung Jawab Negara Terhadap Pelanggaran HAM Berat Paniai Perspektif Teori Efektivitas Hukum Soerjono Soekanto - Muhammad MIftahul Huda; Suwandi Suwandi; Aunur Rofiq (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2022)
Abstract: In Indonesia, cases of human rights violations have occurred since the reign of the Old Order, the New Order, and even the current reform era. In the case of human rights violations in Indonesia, there are several cases of gross human rights violations that have not been resolved until now. Here, one of the cases of gross human rights violations that has not been resolved until now and the author wants to raise is the case of Paniai Papua's human rights. The focus of this paper is related to the implementation of the state in the responsibility of protecting, respecting, and fulfilling human rights in the case of Paniai human rights violations from the perspective of the theory of legal effectiveness. The research method used in this study is a juridical-normative approach, which examines the law from the historical and formal legal aspects. This study uses library data, while the data source is secondary data, namely data obtained through library materials by collecting from various reading sources related to the problem being studied. The research in this paper is a qualitative descriptive analysis. The result of this paper is the state as the holder of the highest sovereignty in implementing the responsibility for respecting, protecting, fulfilling human rights by establishing laws and regulations related to human rights and the Human Rights Court or the Human Rights Court. The implementation of the state's responsibility in respecting, protecting, and fulfilling cases of gross human rights violations in Paniai with the existence of laws and regulations on human rights and the human rights court so far has not been said to be effective because the case has not been resolved until now by looking at the factors that can be used as a measure. the effectiveness or not of such a law.Abstrak: Di Indonesia, kasus pelanggaran HAM sudah terjadi dari masa pemerintahan orde lama, orde baru, bahkan sampai masa reformasi kini. Dalam kasus pelanggaran HAM tersebut di Indonesia terdapat beberapa kasus pelanggaran HAM berat yang sampai kini belum terselesaikan. Di sini salah satu kasus pelanggaran HAM berat yang belum terselesaikan sampai kini dan penulis ingin angkat adalah kasus HAM Paniai Papua. Fokus tulisan ini adalah terkait implemantasi negara dalam tanggung jawab perlindungan, penghormatan, dan pemenuhan HAM dalam kasus pelanggaran HAM Paniai perspektif teori efektivitas hukum. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan yuridis-normatif, yang mengkaji hukum dari aspek sejarah dan legal formal. Penelitian ini menggunakan data perpustakaan, sedangkan sumber datanya adalah data sekunder yaitu data yang diperoleh melalui bahan pustaka dengan cara mengumpulkan dari berbagai sumber bacaan terkait masalah yang sedang dipelajari. Penelitian dalam tulisan ini adalah analisis deskriptif kualitatif. Hasil dari tulisan ini negara sebagai pemegang kedaulatan tertinggi dalam implementasikan tanggung jawab terhadap penghormatan, perlindungan, pemenuhan HAM dengan cara pembentukan peraturan undang-undang yang terkait dengan Hak Asasi Manusia dan Pengadilan Hak Asasi Manusia atau Pengadilan HAM. Pengimplementasi tanggung jawab negara dalam menghormati, melindungi, dan memenuhi kasus pelanggaran HAM berat di Paniai dengan adanya peraturan undang-undang tentang HAM dan pengadilan HAM sampai ini belum bisa dikatan efektif karena belum terselesaikannya kasus tersebut hingga kini dengan melihat faktor-faktor yang dapat dijadikan ukuran efektivitas atau tidaknya suatu hukum tersebut.